Efeitos da deficiência estrogênica na β-oxidação peroxissomal e mitocondrial e no estado redox de fígados de ratas e os efeitos benéficos do Vitex agnus-castus - Vitoriano, Adriana de Souza (2011)
The estrogen deficiency is associated with profound alterations in the lipid metabolism and a higher incidence of metabolic syndrome (MS) and its comorbidities, such as hepatic steatosis or non-alcoholic fatty liver disease (NAFLD. The hormonal replacement therapy (HRT) has proven effective in the treatment of several metabolic disturbs characteristic of MS, including body weight gain, dyslipidemia and NAFLD. However the use of estrogen-progestogen combinations represents health risks of women predisposing factors of cancer or thromboembolic events. This has been stimulated the research of natural products as alternative forms of HRT. Several plants contain substances chemically similar to estrogen ? the phytoestrogens ? that can be used in the treatment of the menopause. One of these plants is Vitex agnus-castus, used for their benefits for menopause complaints, such as hot flushes and night sweat. There are accumulating evidences that estrogen deficiency contributes to the prevalence of NAFLD, not only indirectly by increasing the incidence of MS in postmenopausal women, but also by direct, intrahepatic actions. Thus, considering the possibility of progression of NAFLD to more severe diseases and liver failure, this study aimed to investigate the effects of estrogen deficiency per se and of the treatment with Vitex agnus-castus, on hepatic lipid metabolism. With this purpose, untreated ovariectomized (OVX) rats and OVX treated with Vitex extract (OVX + VA) were evaluated in their liver lipid contents and serum lipid profile, as well as in their mitochondrial and peroxisomal capacities of oxidizing fatty acids. Furthermore the oxidative status of the liver and the activities of enzymes involved in the control of redox status were assessed. Female Wistar rats weighing 130 to 160 g were divided into two groups: ovariectomized (OVX) and sham-operated (control); after eleven weeks, the OVX rats were subdivided into two other groups: untreated ovariectomized (OVX) and OVX treated with Vitex agnus-castus (OVX + VA). After 15 days of treatment the animals were sacrificed and the glycaemia and lipid levels were measured in blood and plasma, respectively. Liver mitochondria and peroxisomes were isolated by differential centrifugation and used for β-oxidation measurements. The mitochondrial generation of ROS (reactive oxygen species) and peroxisomal catalase activity were also evaluated. Liver homogenates were assessed in other parameters indicative of the redox stat e, including the reduced glutathione (GSH) contents and the glucose 6-phosphate dehydrogenase (G6PD) activity, enzyme involved in the GSH red with those found in control rats (sham-operated).The following results w system restoring. The results obtained in these two groups were compaere with those foud in control rats (sham-operated)...cont.